THE DIAGNOSIS OF BRAIN DISEASES USING MAGNETIC RESONANCE IMAGING TECHNIQUES - Berdiyev Behzod Shomurodovich; Djumayev Akbar Anvarovich (KONFERENSIYALAR, 2025)
Аnnotation. The function of magnetic resonance imaging in the diagnosis of neurodegenerative illnesses is reviewed in this article. The problem's applicability and  the  potential  of  several  approaches  are  developed.  Magnetic  resonance imaging  techniques,  both  conventional  and  unconventional,  are  discussed.  This review looks at contemporary MRI methods for early brain illness detection.